Fetal cerebral ventriculomegaly: What do we tell the prospective parents?. (21st November 2022) - Giorgione, Veronica; Haratz, Karina Krajden; Constantini, Shlomi; Birnbaum, Roee; Malinger, Gustavo
Abstract: Fetal cerebral ventriculomegaly is a relatively common finding, observed during approximately 1% of obstetric ultrasounds. In the second and third trimester, mild (≥10 mm) and severe ventriculomegaly (≥15 mm) are defined according to the measurement of distal lateral ventricles that is included in the routine sonographic examination of central nervous system. A detailed neurosonography and anatomy ultrasound should be performed to detect other associated anomalies in the central nervous system and in other systems, respectively. Fetal MRI might be useful when neurosonography is unavailable or suboptimal. The risk of chromosomal and non‐chromosomal genetic disorders associated with ventriculomegaly is high, therefore invasive genetic testing, including microarray, is recommended. Screening for prenatal infections, in particular cytomegalovirus and toxoplasmosis, should also be carried out at diagnosis. The prognosis is determined by the severity of ventriculomegaly and/or by the presence of co‐existing abnormalities. Fetal ventriculoamniotic shunting in progressive isolated severe ventriculomegaly is an experimental procedure. After delivery, ventricular‐peritoneal shunting or ventriculostomy are the two available options to treat hydrocephalus in specific conditions with similar long‐term outcomes. A multidisciplinary fetal neurology team, including perinatologists, geneticists, pediatric neurologists, neuroradiologists and neurosurgeons, can provide parents with the most thorough prenatal counseling. This review outlines the latest evidence on diagnosis and management of pregnancies complicated by fetal cerebral ventriculomegaly. Key points: What's already known about this topic? Fetal ventriculomegaly is a relatively common finding on obstetric ultrasound examinations. The diagnostic workup includes genetic testing, infection screening, detailed anatomy ultrasound and neurosonography. The prognosis varies according to the severity of dilation and/or to the presence of other anomalies. What does this review add? This review summarizes the most important aspects that an obstetrician should know in terms of diagnostic work‐up and prenatal counseling. The best prenatal counseling would be provided by a multidisciplinary fetal neurology team.